2021
DOI: 10.1002/advs.202101329
|View full text |Cite
|
Sign up to set email alerts
|

The m6A Readers YTHDF1 and YTHDF2 Synergistically Control Cerebellar Parallel Fiber Growth by Regulating Local Translation of the Key Wnt5a Signaling Components in Axons

Abstract: Messenger RNA m 6 A modification is shown to regulate local translation in axons. However, how the m 6 A codes in axonal mRNAs are read and decoded by the m 6 A reader proteins is still unknown. Here, it is found that the m 6 A readers YTHDF1 and YTHDF2 are both expressed in cerebellar granule cells (GCs) and their axons. Knockdown (KD) of YTHDF1 or YTHDF2 significantly increases GC axon growth rates in vitro. By integrating anti-YTHDF1&2 RIP-Seq with the quantitative proteomic analysis or RNA-seq after KD of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Ythdf2 fl/fl mice were reported previously ( Yu et al, 2021b ). Six3-cre ( Furuta et al, 2000 ), Thy1-GFP ( Feng et al, 2000 ), and Rosa26-eYFP ( Srinivas et al, 2001 ) mice were from Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ythdf2 fl/fl mice were reported previously ( Yu et al, 2021b ). Six3-cre ( Furuta et al, 2000 ), Thy1-GFP ( Feng et al, 2000 ), and Rosa26-eYFP ( Srinivas et al, 2001 ) mice were from Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…E15.5 retinal neurons were cultured and infected with lentiviral sh Ythdf2 or shCtrl. Sample collection and lysis, protein and peptide preparation were performed following procedures reported previously ( Yu et al, 2021b ). Proteins with fold changes greater than 1.3 and p values less than 0.05 were considered to be regulated by YTHDF2 KD with statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DF1 enhances the translation efficiency of target transcripts in two ways: first, it accelerates the occupancy of the ribosome to methylated mRNA; second, it interacts with initiation factors to promote expression of target mRNA. DF2 was found to regulate the translation of m6A-modified mRNA by cooperating with DF1 or by individually binding to its m6A sites on its 3′UTR [ 31 , 32 ]. DF3 has been reported to primarily regulated the initiation of m6A-methylated mRNA translation by interacting with DF1 in cytoplasmic [ 33 ].…”
Section: General Functions Of Yth Domain-containing Proteinsmentioning
confidence: 99%
“…Sheng et al found that DF2 individually acts as a tumor promoter to enhance tumor growth via facilitating 6PGD mRNA translation [ 31 ]. DF2 also plays its translation regulation function through synthetizing with DF1, and regulates the Wnt5a pathway by promoting the local translation of GC axons, so as to control the development of cerebellar parallel fibers [ 32 ]. Shi et al demonstrated for the first time that DF3 promoted mRNA translation by interacting with ribosomal 40S/60S subunits.…”
Section: General Functions Of Yth Domain-containing Proteinsmentioning
confidence: 99%